Biopolitical Citizenship in the Immigration Adjudication Process. (4th November 2014) - Lakhani, Sarah Morando; Timmermans, Stefan
Abstract : We apply the concept of "biopolitical citizenship" to show how and with what consequences biology and medicine are mobilized as political techniques in the legal immigration procedures of permanent residency acquisition and family reunification. Medical examinations and DNA testing are employed by the U.S. state as objective sorting criteria in the immigration legal process. Based on qualitative examination of immigrants' and their attorneys' participation in the legalization process, we demonstrate how these biological screening mechanisms create added uncertainty and problems that disproportionately affect particular people. In this context, aspiring citizens undergo biological evaluations that appear transparent, objective, and democratic. However, because of how evaluations are structured, they actually lower the chances of certain individuals to succeed in their citizenship endeavors.